PEMBELAJARAN KETERAMPILAN MENULIS BERBASIS PROSES MENULIS DAN TEORI PEMEROLEHAN BAHASA - Herman Budiyono (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2012)
This article aim to explain skill study to write being based on process to write and the language acquisition theory. For the purpose, there is fundamental three things elaborated at this article, that is (1) process writes, (2) language acquisition, and (3) skill study writes. Description firstly covers (a) the process theory writes and (b) process principles writes. Including second description (a) the language acquisition theory and (b) language acquisition principles. Description third covers (a) skill study writes being based on process principle to write and (b) skill study writes being based on language acquisition principle.Keywords: skill study writes, process writes, language acquisition